TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PEMBUNUHAN (STUDI KASUS NOMOR 23/PID.B/2014/PN) - Murary, Weron; Damhuri, Nofri (Ensiklopedia of Journal, 2021)
This research wants to know the application of law to murder crime in decision Number 23/Pid.B/2014/ PN.F and to know judge's consideration in imposing sanction to murder case Number 23/Pid.B/2014/PN.F. The results showed that the application of material criminal law to murder case Number 23 / Pid.B / 2014 / PN.PF, based on the results of investigation and testimony of witnesses and the accused of the defendant proved to have violated Article 338 of the Criminal Code regulating the murder. In this case, the defendant is found guilty according to law and must be accountable for his actions and must be sentenced accordingly with the actions of the defendant, there is nothing that can release the defendant from criminal responsibility, both as justification and reasons of forgiveness and judge consideration in imposing sanction criminal offenses against perpetrators in Case Number 23 / Pid.B / 2014 / PN.F, as appropriate (related to length of sentence). With the fulfillment of all the elements of the article in the indictment of the second indictment of Article 338 of the Criminal Code, as well as the statements of the witnesses with each other plus the judge's conviction. The legal considerations imposed by the judge on the defendant in the case have been appropriate.